Adaptation of parental expectation of children’s future scale in Indonesian version - Solichah, Novia; Fardana, Nur Ainy; Samian, Samian (Intelektual Pustaka Media Utama, 2025)
Parental expectations play a crucial role in shaping a child's developmental trajectory, serving as a primary motivator for the attainment of future aspirations. Researchers conducted a literature review on parental expectations toward their children, utilizing ten instruments developed in journal literature from 2008 to 2020. Of particular interest was the Parent Questionnaire containing the Chinese Parental Expectation on Child’s Future Scale (CPECF), it constitutes a fundamental framework for comprehending parental anticipations in the realm of child development. This study aimed to adapt and validate the PECF scale, employing established validation procedures endorsed by the International Test Commission. Initially, a cohort of 987 parents participated; however, after data cleansing procedures aimed at eliminating incomplete responses and ensuring accuracy, the analysis focused on 593 respondents. The participants’ ages ranged from 21 to 78 years, with a mean age of 35.93 years. Confirmatory Factor Analysis revealed 17 valid and reliable items. The model demonstrated a good fit. These findings suggest that the PECF scale effectively measures parental expectations, aligning with the original scale. It is anticipated that this scale will serve as a valuable tool for research concerning parental expectations in Indonesia, aiding in understanding and addressing the dynamics.